Regional film in the dynamics of the national film industry - Puspitasari, Lilis; Bajari, Atwar; Hidayat, Dadang Rahmat; Cho, Sung Kyum (Universitas Padjadjaran, 2024)
Background: In the last ten years, the Indonesian film industry has experienced significant growth. The national film industry and the regional film industry, one of which is indie films produced in the city of Makassar. The development of films in Makassar began to receive national public attention with the explosion of the film Uang Panai in 2016. Also, in 2017, the success of the movie Silariang received an audience of 183.340 people. Purpose: Examining the impact of Makassar-produced films on the dynamics of Indonesia's domestic film industry is the main objective of this study, including examining its impact on cultural identity, economic variables, and its role in enhancing the uniqueness of national film. Methods: This study employs a qualitative methodology and gathers data through content analysis, observation, and interviews. Results: According to the study's findings, regional films—like those made in Makassar—are essential to the growth and advancement of the country's film industry. This demonstrates how crucial it is to acknowledge and encourage filmmaking outside of the major industrial hubs. Conclusion: Research shows that regional films have the potential to positively impact economic growth, especially in the regions where they are produced. It encourages the creative economy, creates local employment opportunities, and offers direct and indirect financial benefits. Implications: There is a need to recognize and promote regional films to encourage the diversity of Indonesian films; this study is also expected to provide a comprehensive understanding of the relationship between regional films and the dynamics of Indonesian films.